(untitled) (AUN INTERNATIONAL CONFERENCE, 2025)
Digital governance is often celebrated for enhancing efficiency, transparency, and modernization, yet in disruptive and under-resourced contexts, it can also accelerate organizational forgetting. This paper advances a conceptual framework that theorizes memory loss in digital transformation as an active, sociotechnical process rather than a passive decline. The framework distinguishes four interrelated forms of forgetting, procedural, relational, epistemic, and structural, that capture how digital systems can marginalize tacit practices, erase legacy infrastructures, and silence alternative epistemologies. Presented here as a conceptual foundation for ongoing research, the framework will be empirically validated and refined through a planned multiple-case study of Nigerian universities. The ultimate aim is to contribute to the development of adaptive digital governance models that are sensitive to institutional memory, epistemic diversity, and organizational resilience in contexts of disruption. Thus, this paper seeks to (1) articulate a diagnostic lens for analyzing organizational forgetting in digital governance, and (2) outline the trajectory through which this framework will be tested and validated.